Compositional differences between Copaxone and Glatopa are reflected in altered immunomodulation ex vivo in a mouse model. Issue 1 (23rd November 2017) - Grossman, Iris; Kolitz, Sarah; Komlosh, Arthur; Zeskind, Benjamin; Weinstein, Vera; Laifenfeld, Daphna; Gilbert, Adrian; Bar‐Ilan, Oren; Fowler, Kevin D.; Hasson, Tal; Konya, Attila; Wells‐Knecht, Kevin; et al.
Abstract: Copaxone (glatiramer acetate, GA), a structurally and compositionally complex polypeptide nonbiological drug, is an effective treatment for multiple sclerosis, with a well‐established favorable safety profile. The short antigenic polypeptide sequences comprising therapeutically active epitopes in GA cannot be deciphered with state‐of‐the‐art methods; and GA has no measurable pharmacokinetic profile and no validated pharmacodynamic markers. The study reported herein describes the use of orthogonal standard and high‐resolution physicochemical and biological tests to characterize GA and a U.S. Food and Drug Administration–approved generic version of GA, Glatopa (USA‐FoGA). While similarities were observed with low‐resolution or destructive tests, differences between GA and USA‐FoGA were measured with high‐resolution methods applied to an intact mixture, including variations in surface charge and a unique, high‐molecular‐weight, hydrophobic polypeptide population observed only in some USA‐FoGA lots. Consistent with published reports that modifications in physicochemical attributes alter immune‐related processes, genome‐wide expression profiles of ex vivo activated splenocytes from mice immunized with either GA or USA‐FoGA showed that 7–11% of modulated genes were differentially expressed and enriched for immune‐related pathways. Thus, differences between USA‐FoGA and GA may include variations in antigenic epitopes that differentially activate immune responses. We propose that the assays reported herein should be considered during the regulatory assessment process for nonbiological complex drugs such as GA.